von Willebrand Factor (vWf) as a Plasma Marker of Endothelial Activation in Diabetes: Improved Reliability with Parallel Determination of the vWf Propeptide (vWf:AgII) - Vischer, Ulrich; Emeis, Jef J.; Bilo, Henk J. G.; Stehouwer, Coen D. A.; Thomsen, Claus; Rasmussen, Ole; Hermansen, Kjeld; Wollheim, Claes B.; Ingerslev, Jørgen (Thrombosis and Haemostasis, 1998)
Elevated plasma von Willebrand factor (vWf) levels are found in diabetes and other vasculopathies, and predict cardiovascular mortality. vWf is stored and released from endothelial cell secretory granules, along with equimolar amounts of its propeptide (vWf:AgII). In the present study, we examined plasma propeptide levels as a marker of endothelial secretion in vivo, using an ELISA based on monoclonal antibodies. vWf but not propeptide levels are influenced by blood groups, explaining in part the smaller variation in plasma propeptide levels among normal individuals. In both controls and insulin-dependent diabetic patients, we found a close correlation between propeptide and immunoreactive vWf levels (r2 = 0.54, p <0.0001). vWf and propeptide were elevated in patient subgroups with microalbuminuria or overt diabetic nephropathy, whereas only the propeptide was significantly elevated in the normoalbuminuric subgroup. This observation suggests that in conjunction with vWf, propeptide measurements may improve the identification of endothelial activation, which occurs frequently even without increased urinary albumin excretion. In 12 NIDDM patients, a 3-week diet enriched in monounsaturated fat (MUFA) resulted in parallel decreases in vWf (-22%, p <0.05) and propeptide (-17%, p <0.05) levels, indicating that the experimental diet affected endothelial secretion rather than vWf catabolism. A carbohydrate-enriched control diet did not significantly influence either marker.Our results suggest that concomittant determinations of plasma vWf and propeptide are useful tools to assess endothelial activation in vivo, and reinforce our previous conclusion that a diet rich in MUFA can improve endothelial function in NIDDM.